Influential diamagnetic magnesium (Mg2+) ion substitution in nano-spinel zinc ferrite (ZnFe2O4): Thermal, structural, spectral, optical and physisorption analysis - Somvanshi, Sandeep B.; Khedkar, Mangesh V.; Kharat, Prashant B.; Jadhav, K.M. (Ceramics international, 2020)
Nano-spinel zinc ferrites (ZnFe2O4) with substitution of diamagnetic magnesium (Mg2+) ions were synthesized using solution-gelation (sol-gel) self ignition route. The thermal, structural, spectral, optical and N2-physisorption properties of the prepared Zn–Mg ferrite nanoparticles were analyzed by standard characterization techniques. The temperature dependent spinel phase formation and percentage weight loss was studied by thermogravimetric and differential thermal analysis (TG-DTA). The analysis of the room temperature X-ray diffraction (XRD) patterns showed the formation of cubic spinel structure with single phase in the Zn–Mg ferrites. The crystallite size decreasing from 27 nm to 20 nm with Mg2+ substitution confirmed the nanocrystalline formation of the Zn–Mg ferrites. The two characteristics vibrational modes of interstitial sub-lattice sites corresponding to the spinel structure were observed within the desired wavelength range of the FT-IR spectra. The optical band gap values estimated from the UV–Visible data analysis is found to be in the scope of 1.96 eV–2.39 eV. The photoluminescence (PL) spectra showed the broader emission band in the visible region (around 525 nm) for all the samples of Zn–Mg ferrites. The BET isotherms were recorded by the N2 adsorption-desorption and the surface area, pore volume, average pore radius etc surface parameters were deduced. The BET surface area and average pore radius values were obtained in the range of 5.6–24.8 m2/gm and 2.61–4.52 nm respectively.